2012
DOI: 10.2169/internalmedicine.51.7304
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Relapse of Whipple's Disease

Abstract: A 50-year-old man presented with a 12 kg weight loss in 8 months. Upper gastrointestinal endoscopy findings showed strong erosion and diffuse bleeding in the duodenum. Histopathological findings showed PAS staining-positive macrophages consistent with Whipple's disease. He was treated with trimethoprimsulfamethoxazole. His condition initially improved. However, during his 6-year course of treatment he developed a central nervous system relapse. Tropheryma whipplei DNA was detected by a polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Given the broad differential diagnoses and the disease's rarity in Japan, Whipple's disease can be difficult to diagnose ( 6 , 9 ). The differential diagnoses include inflammatory rheumatic diseases, malabsorption with small intestine involvement (e.g., celiac disease, sarcoidosis, and lymphoma), Addison's disease, and connective tissue disorders ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the broad differential diagnoses and the disease's rarity in Japan, Whipple's disease can be difficult to diagnose ( 6 , 9 ). The differential diagnoses include inflammatory rheumatic diseases, malabsorption with small intestine involvement (e.g., celiac disease, sarcoidosis, and lymphoma), Addison's disease, and connective tissue disorders ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We performed repeated follow-up gastrointestinal endoscopy, confirming that the changes in the duodenal mucosa improved in the early stage of treatment, whereas macrophage infiltration in the lamina propria of the duodenum persisted. Uryu et al reported a case with neurologic recurrence of Whipple's disease, where the accumulation of macrophages in the lamina propria of the duodenum continued for six years, even after the symptoms had disappeared ( 9 ). Although the relevance of this finding to the clinical course and risk of recurrence is unknown, it may suggest that macrophage replication and the anti-inflammatory function of the lamina propria remain abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…Whipple's disease (WhD) is a rare but treatable infectious disease from Tropheryma whipplei (TW), with an estimated incidence of 0.4 to 1.0 per 1,000,000 a year . The brain follows the gastrointestinal tract as the second major site of involvement, with CNS involvement on postmortem found in up to 50% of cases, most frequently in a periventricular and periaqueductal distribution .…”
mentioning
confidence: 99%
“…The brain follows the gastrointestinal tract as the second major site of involvement, with CNS involvement on postmortem found in up to 50% of cases, most frequently in a periventricular and periaqueductal distribution . The percentage of clinical CNS involvement varies considerably, ranging from 6% to 63%, with most estimates of 10%‐43%. In approximately 5% of cases, the initial manifestations are purely neurological .…”
mentioning
confidence: 99%
“…Whipple disease was considered as a potential diagnosis, although only a few patients with this disease had been reported in Japan. 3 5 However, the absence of periodic acid-Schiff (PAS)–positive macrophages in duodenal biopsy argued against Tropheryma whipplei infection. Subsequently brain biopsy was performed and the potential infectious organism was ultrastructurally and genetically characterized.…”
Section: Methodsmentioning
confidence: 99%